2021
DOI: 10.3389/fcvm.2021.647953
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Analysis of Competitive Endogenous RNA Regulatory Networks in Coronary Artery Disease

Abstract: Background: Coronary artery disease (CAD) is the leading cause of cardiovascular death. The competitive endogenous RNAs (ceRNAs) hypothesis is a new theory that explains the relationship between lncRNAs and miRNAs. The mechanism of ceRNAs in the pathological process of CAD has not been fully elucidated. The objective of this study was to explore the ceRNA mechanism in CAD using the integrative bioinformatics analysis and provide new research ideas for the occurrence and development of CAD.Methods: The GSE11307… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Another 17 transcription factors are not studied for their association with CAD. In addition, there is growing evidence that competitive endogenous RNAs (ceRNAs) play a key role in CAD and cancer ( 69 ). However, there is still a lack of ceRNA networks that can predict the diagnosis and treatment of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Another 17 transcription factors are not studied for their association with CAD. In addition, there is growing evidence that competitive endogenous RNAs (ceRNAs) play a key role in CAD and cancer ( 69 ). However, there is still a lack of ceRNA networks that can predict the diagnosis and treatment of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The "limma" package, a package for analyzing gene expression data generated by microarray or RNA-seq technology (19), was used to obtain the DEGs in the GSE9476 dataset. The screening criteria was: p value < 0.05 and |log 2 FoldChange| > 0.5 (20,21). The "VennDiagram" package (22) was applied to visualize the differentially expressed ERGs (DE-ERGs).…”
Section: Identification Of M6a -Related Differentially Expressed Ergsmentioning
confidence: 99%
“…revealed that TMEM184B is one of the five hub genes involved in the progression of ANCA-GN through immune-related signalling pathways. Similarly, Ji et al26 found that TMEM184B might crucially influence the occurrence and development of coronary artery disease by participating in the OIP5-AS1-miR-25-3p-TMEM184B ceRNA regulatory network. The roles of TMEM184B in the biological processes of cancer are also gaining attention.…”
mentioning
confidence: 91%